Efficacy and Safety of Antimalarial as Repurposing Drug for COVID-19 Following Retraction of Chloroquine and Hydroxychloroquine - Latarissa IR; Khairinisa MA; Iftinan GN; Meiliana A; Sormin IP; Barliana MI; Lestari K (Clinical Pharmacology: Advances and Applications)
Irma Rahayu Latarissa,1,2 Miski Aghnia Khairinisa,1 Ghina Nadhifah Iftinan,2 Anna Meiliana,1,3 Ida Paulina Sormin,4,5 Melisa Intan Barliana,6,7 Keri Lestari1,2,7 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Medication Therapy Adherence Clinic (MTAC), Universitas Padjadjaran, Sumedang, Indonesia; 3Prodia Clinical Laboratory, Central Jakarta, Indonesia; 4Faculty of Pharmacy, University of 17 August 1945 Jakarta, Jakarta, Indonesia; 5Prodia Diacro Laboratory, Jakarta, Indonesia; 6Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 7Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, IndonesiaCorrespondence: Keri Lestari, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM. 21, Jatinangor, 45363, Indonesia, Email lestarikd@unpad.ac.idAbstract: Various repurposing drugs have been tested for their efficacy on coronavirus disease 2019 (COVID-19), including antimalarial drugs. During the pandemic, Chloroquine (CQ) and Hydroxychloroquine (HCQ) demonstrated good potential against COVID-19, but further studies showed both drugs had side effects that were more dangerous than the efficacy. This made World Health Organization (WHO) ban the usage for COVID-19 patients. In this context, there is a need to explore other antimalarial drugs as potential therapies for COVID-19. This study provides a descriptive synthesis of clinical trials evaluating antimalarial drugs for COVID-19 treatment conducted after the withdrawal of CQ and HCQ. The method was a literature study using the keywords “antimalarial”, “COVID-19”, “SARS-CoV-2”, “clinical trial”, and “randomized controlled trial” on the MEDLINE, Scopus, and Cochrane databases. Inclusion criteria were published clinical trials with randomized controlled trials (RCTs) on the efficacy and safety of single antimalarial drugs for COVID-19, published in English and excluding combination therapies. The results showed 3 antimalarial drugs, namely Quinine Sulfate (QS), Atovaquone (AQ), and Artemisinin-Piperaquine (AP), had gone through clinical trial to assess efficacy and safety against COVID-19 patients. Out of the 3 drugs, only AP showed significant results in the primary outcome, which was the time required to reach undetectable levels of SARS-CoV-2. Furthermore, the intervention group took 10.6 days, and the control group took 19.3 days (p=0.001). Based on this review, AP showed significant potential as a therapy in the fight against COVID-19.Keywords: randomized controlled trial, Quinine Sulfate, Atovaquone, Artemisinin-Piperaquine, SARS-CoV-2